Screening of vitamin D and calcium concentrations in neonates of mothers at high risk of vitamin D deficiency - Sheikh Arif M. Kozgar; Paul Chay; Craig F. Munns (BMC, 2020)
Abstract Objective The aim of this study was to determine, retrospectively, the serum 25OHD and calcium concentrations of screened neonates of mothers at high risk of 25OHD deficiency and examine whether their measurement contributes to the management of these neonates. Methods Serum 25OHD and calcium concentrations from 600 samples of umbilical cord blood or venous blood collected from neonates over a 12-month period were analysed. Results There was a high prevalence of vitamin D insufficiency (27.6%, 30-50 nmol/L) and deficiency (21.3%, < 30 nmol/L) in neonates from high-risk maternal groups. There was a statistically positive but weak correlation (ρ = 0.22, P < 0.0001) between 25OHD and serum calcium. Only 7 neonates out of 569 (1.2%) had calcium concentrations in the hypocalcaemic range; however, a significant number (47.6%) were reported to be in the hypercalcaemic range. Nearly all of these were venous samples collected in first 24 h after birth. Conclusion Vitamin D deficiency is prevalent in neonates of high-risk mothers but the risk of hypocalcaemia due to vitamin D deficiency at birth is low. Screening neonates entails blood testing which can cause distress to neonates and their parents, substantial imposition on staff and financial burden on the health care system. Vitamin D supplementation of these neonates from birth without routine screening appears more reasonable. Also, the data from this study suggest that the paediatric reference range for corrected calcium concentrations in neonates should be re-evaluated.